ANTIQUITY IN UKRAINIAN MYTHO-IDEOLOGY OF 1920s–1930s - Halchuk, Oksana (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.142 The artistic «reaction» to post-revolutionary reality with its two discourses, modern and socialist, has predetermined the interpretation of antique mythologemes as ideologues in Ukrainian literature of the 1920s and 1930s. From the point of view of the development of the phenomenon of Ukrainian antiquity, during this period we observe an intensified elaboration of cosmological, existential and aesthetic motives as a meta-language which aimed at constructing of the contraversional images of the new sacralized world, its characteristics and perspectives. The modernist discourse focuses mainly on the triad of «humanism — nationalism — Europeanism». Ideologemes of modernist poets associate with aesthetization, a dominant feature of their program, and revolve around the problem of “the artist (Orpheus, Cassandra, etc.), who lives during the Iron Age”. Neoclassicists and symbolists redirect in their poetry the motif of fatum into a motif of fatum of a totalitarian state, and change the traditional interpretation of the Prometheus-Tyranborian into an image of the degraded Prometheus. Instead, futurists and neo-romantics prefer the mytho-motive (later used by the socialist-realist discourse as well) of modernity as the battle of the Titans, in which Prometheus becomes the epitome of the rebellious proletariat. The social-realist discourse, while formally distancing itself from the world artistic tradition, implicitly reciprocates it, turning the precedent motives and images into ideologemes; e.g., the motif of titanomachy to characterize the present; new leaders of the state are subconsciously perceived as new Olympians who has conquered the chaos and are build a new Cosmos. In this case, the myth of the Iron Age is interpreted in a positive sense; the image of the enemy — the hydra of counter-revolution — «nourishes» the justification of repression. Accordingly, they cultivate the «hero of the day», the uncompromising Prometheus-Tyranborian or Spartacus, or create a collective image of the «leader of the revolution» as a transformation of the centaur. Thus, antique mythology, reinterpreted in the context of ideological and aesthetic programs of different discourses of Ukrainian literature in the 1920s and 1930s, becomes the basis of different variants of mytho-ideology. .